The Congressional Journal of Barber B. Conable, Jr., 1968-1984 - Conable, Barber B. (Book collections on Project MUSE., 2021)
"Barber Conable was one of the most esteemed members of Congress of his era. Elected to the House of Representatives from a rural New York district in 1964, the Republican Conable served ten terms and was on multiple occasions voted the most respected member of the House in polls of staffers and reporters. Known for his integrity, Conable accepted no campaign contribution of greater than $50, even when he faced a strong Democratic challenger in the Watergate landslide year of 1974. As ranking minority member of the House Ways and Means Committee, Conable played a central role in the crafting of tax and trade policy, but he viewed his frank and thoughtful journal-never before published in any form-as one of his major achievements. The journal was a source for Bob Woodward and Carl Bernstein's The Final Days about the Watergate scandal, but Conable did not let them read the manuscript for themselves, "because I had so much other stuff in there that was sensitive in nature." The Conable journal comprises 16 volumes covering the years 1968-1984. Carefully edited by Bill Kauffman, this selection offers a uniquely honest and ruminative window into the world of Congress during an especially fraught period in American history, spanning the presidencies of Richard Nixon to Ronald Reagan. Includes a foreword by Albert R. Hunt, who worked for the Wall Street Journal's Washington bureau for 35 years, who writes, "I've never spent time with a more thoughtful, and basically generous, politician.""--